2002
DOI: 10.1080/1366825021000008602
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual analysis of communicative spontaneity

Abstract: Communicative spontaneity is reported to present a signi cant problem for individuals with high support needs. Examination of literature addressing communicative spontaneity reveals conceptually opposing views of the phenomenon. Both the binary and the continuum conceptualisations are examined in this paper in speci c relation to their logical consistency, explanatory power and limitations. It is argued that the continuum conceptualisation offers much greater explanatory power and facilitates understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 76 publications
0
26
0
Order By: Relevance
“…Third, it is difficult to practically identify interoceptive stimuli (Sigafoos and Reichle 1993), and this makes the measurement of those stimuli problematic. Finally, there is a lack of detail provided on operationalizing Halle's continuum (Carter and Hotchkis 2002). Considering these issues, Carter and Hotchkis (2002) concluded that Halle's model seems to be more useful as an explanatory tool for conceptualizing continuum theory rather than a practical instrument for the measurement of spontaneity.…”
Section: Halle's Modelmentioning
confidence: 96%
See 4 more Smart Citations
“…Third, it is difficult to practically identify interoceptive stimuli (Sigafoos and Reichle 1993), and this makes the measurement of those stimuli problematic. Finally, there is a lack of detail provided on operationalizing Halle's continuum (Carter and Hotchkis 2002). Considering these issues, Carter and Hotchkis (2002) concluded that Halle's model seems to be more useful as an explanatory tool for conceptualizing continuum theory rather than a practical instrument for the measurement of spontaneity.…”
Section: Halle's Modelmentioning
confidence: 96%
“…Second, the degree of spontaneity is measured on a continuum in terms of the degree of intrusiveness or obviousness of the controlling stimuli. Finally, adopting a continuum approach to the conceptualization and analysis of spontaneity potentially offers much greater insight into the circumstances under which communication occurs and may have important implications for intervention (Carter and Hotchkis 2002). However, operationalizing this continuum model is problematic.…”
Section: Continuum Conceptualizationmentioning
confidence: 97%
See 3 more Smart Citations